Adaptations of semen characteristics and sperm motility to harsh salinity: Extreme situations encountered by the euryhaline tilapia Sarotherodon melanotheron heudelotii (Dumeril, 1859) - Legendre, Marc; Alavi, Sayyed Mohammad Hadi; Dzyuba, Boris; Linhart, Otomar; Prokopchuk, Galina; Cochet, Christophe; Dugué, Rémi; Cosson, Jacky (Theriogenology, 2016)
In most teleost fishes, sperm cells are quiescent in the seminal plasma and are activated by either a drop (fresh water fish) or an increase in osmolality (marine fish) when released in the water. It is most interesting to examine how the mechanisms of sperm motility activation can adapt to a broad range of salinities, as applies to some euryhaline species, and particularly to the tilapia Sarotherodon melanotheron heudelotii, which can reproduce at salinities from 0 up to 120 in the wild. Here, the gonado-somatic index, semen characteristics, and the osmotic and ionic requirements of sperm motility activation were compared in S. m. heudelotii reared in fresh water (FW), sea water (SW), or hypersaline water (HW; salinities of 0, 35, and 70, respectively). No salinity-dependent differences were found in gonado-somatic index or semen characteristics, except for an increase of seminal plasma osmolality with increasing salinity (from 318 to 349 mOsm kg(-1) in FW and HW fish, respectively). The osmolality range allowing the highest percentages of sperm activation broadened and shifted toward higher values with increasing fish ambient salinity (150-300, 300-800, and 500-1200 mOsm kg(-1), for FW, SW, and HW fish, respectively). Nevertheless, at the three fish rearing salinities, sperm could be activated in media that were hypotonic, isotonic, or hypertonic relative to the seminal plasma, at least when some calcium was present above a threshold concentration. The [Ca(2+)] required for the activation of S. m. heudelotii sperm is (1) higher in fish reared at a higher salinity (2) higher in hypertonic than that in hypotonic activation media, whatever the fish rearing salinity, and (3) higher in the presence of Na(+) or K(+), the negative effects of which increased with an increase in fish rearing salinity. The [Ca(2+)]/[Na(+)] ​ ratios allowing for maximal sperm motility in SW or HW fish are close to those observed in natural environments, either in sea or hypersaline waters. In comparison to most teleosts with external fertilization, the total duration of sperm motility in S. m. heudelotii was exceptionally long (>2 hours regardless the fish rearing salinities). The decrease in sperm activity with increasing time since activation did not result from limiting energy reserves, as the addition of calcium in the activation medium caused most spermatozoa to become motile again. The comparison of sperm characteristics of S. m. heudelotii acclimated from FW to SW or HW with those of fish maintained all lifelong at their native salinity showed that adaptive responses were completed within 2 months or less.
Keywords: salinita; Animals; Salt Tolerance; cichlidy; spermie; tolerance k soli; Semen; osmotický tlak; Spermatozoa; Osmotic Pressure; motilita spermií; sperma; Cichlids; Male; Sperm Motility; Cell Survival; Salinity; mužské pohlaví; zvířata; viabilita buněk